The Antivirulence Mechanisms of Phytate Against Pathogenic Bacteria in Skin Infections - Nabilatul Zhofiroh; Rian Ka Praja; Elsa Trinovita; Ysrafil Ysrafil; Ranintha BR Surbakti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Skin infections caused by the bacteria Staphylococcus aureus, Streptococcus pyogenes, and Propionibacterium acnes are often a common health problem. One treatment is antibiotics, but the cases of antibiotic resistance are increasing. Thus, new treatment alternatives are needed. This study aimed to analyze the molecular mechanism of phytate antivirulence against pathogenic bacteria of skin infection. This study used a bioinformatics approach involving analysis of phytate interactions with bacterial virulent proteins via STITCH, functional classification of proteins with VICMpred, and prediction of virulence properties using VirulentPred. B-cell and MHC epitopes were analyzed using IEDB, while protein subcellular location was determined through PSORTb. The results showed that phytate interacted specifically with virulent proteins in all three bacteria, most of which functioned in cellular and metabolic processes. These virulent proteins also have immunologically relevant epitopes. Subcellular location analysis showed that phytate protein targets were dispersed in the cytoplasmic membrane and cytoplasm. These findings indicated that phytate has a significant antivirulence mechanism by targeting virulent proteins of skin pathogenic bacteria, thus potentially becoming a therapeutic agent to treat skin infections while reducing antibiotic resistance.